Electric Power Bid Determination and Evaluation for Price Taker Units under Price Uncertainty - Yucekaya, Ahmet; Valenzuela, Jorge (International Journal of Energy Economics and Policy, 2021)
Power companies aim to maximize their profit which is highly related to the bidding strategies used. In order to sell electricity at high prices and maximize their profit, power companies need suitable bidding models that consider power operating constraints and price uncertainty within the market. Price taker units have no power to affect the prices but need to determine their best bidding strategy to maximize their profit assuming a quadratic cost function and uncertain market prices. Price taker units also need to evaluate their bidding strategy under different price scenarios. In this paper, we first model the bidding problem for a price taker unit and then propose quadratic programming, nonlinear programming and marginal cost based bidding models under price uncertainty. We use case studies to study the computation burden and limitation to reach a solution. We also propose a simulation methodology to evaluate the performance of each bidding strategy for different market prices in an effort to help decision makers to assess their bidding decisions. Keywords: Bidding, nonlinear programming, quadratic programming, simulation, electricity markets JEL Classifications: L94, D44, D47, E17 DOI: https://doi.org/10.32479/ijeep.11382